KEEFEKTIFAN URUTAN PEMBELAJARAN KETERAMPILAN GERAK RENANG - F.X. Sugiyanto (Jurnal Cakrawala Pendidikan, 2011)
Abstract: The Effectiveness of Learning Sequences in Swimming Skills. This study aims to investigate the appropriateness and effectiveness of learning sequences in swimming skills after the students mastered the crawl stroke. The sequences were that from the crawl stroke to the breast stroke and that from the crawl stroke to the back stroke. This study was a quasi-experimental study using the pretest-posttest group design. The population comprised students of the Faculty of Sports Sciences, Yogyakarta State University. The sample was selected using the purposive sampling technique. The results showed that the sequence from the crawl stroke to the back stroke was more efficient than that from the crawl stroke to the breast stroke in terms of the mastery of swimming skills. Keywords: learning sequences, crawl stroke, back stroke, breast stroke